2018
DOI: 10.1055/a-0741-7075
|View full text |Cite
|
Sign up to set email alerts
|

Hip Taping Positively Alters Running Kinematics in Asymptomatic Females

Abstract: Greater functional knee valgus (FKV) is thought to contribute to a greater risk of sustaining overuse running injuries. The hip is commonly implicated in greater functional knee valgus, but no studies have investigated the effects of hip taping on running kinematics. The present study investigated whether or not hip taping altered hip and knee kinematics compared to sham and no taping in female runners demonstrating excessive functional knee valgus. Lower limb stance-phase kinematics were collected from 23 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Additionally, the coronal plane hip kinematics showed a significant decrease in peak hip abduction angle in the KTT compared to the NT condition in male participants. This is supported by Masters et al [24] who showed a significant decrease in hip adduction and internal rotation angles throughout stance when a rigid tape was applied to the hip.…”
Section: Discussionmentioning
confidence: 53%
“…Additionally, the coronal plane hip kinematics showed a significant decrease in peak hip abduction angle in the KTT compared to the NT condition in male participants. This is supported by Masters et al [24] who showed a significant decrease in hip adduction and internal rotation angles throughout stance when a rigid tape was applied to the hip.…”
Section: Discussionmentioning
confidence: 53%
“…A total of 28 studies assessed running, 13 involving treadmill running and 15 surface running. Among these studies, ten focused on the effects of different shoes on running biomechanics, [9][10][11][12][13][14][15][16][17][18] three studies examined specific physical interventions, [19][20][21] three studies assessed various gait modifications, [22][23][24] three evaluated foot biomechanics, [25][26][27] two explored the effects of fatigue, 28,29 and two investigated studies the effects of sex. 30,31 Additionally, single studies examined the effects of different surfaces, 32 hamstring flexibility, 33 pertubations, 34 running with different loads, 35 and the differences between transition running and isolated running in triathlon Table 1).…”
Section: Runningmentioning
confidence: 99%
“…Additionally, one study evaluated the inter-individual and intra-individual variability during a squat (Table 4). 70 The median number of participants was 15 [9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Squattingmentioning
confidence: 99%
See 1 more Smart Citation